A method for controlling the particle size and morphology of a special ink-grade titanium dioxide primary product by the sulfuric acid method

CN117902622BActive Publication Date: 2026-10-16CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410080667.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2026-10-16
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

[0006]针对现有技术的不足,本发明提出油墨专用硫酸法钛白初品粒度形貌控制方法,以解决现有的钛白初品粒径精确控制方法难以满足高端油墨专用钛白需求

Benefits of technology

[0017] The beneficial effects of this invention are as follows: The method for controlling the particle size and morphology of sulfuric acid process titanium dioxide primary product for ink production proposed in this invention includes three steps: salt treatment and addition, slurry calcination, and cooling. By adjusting parameters such as the type and amount of salt treatment agent added, calcination steps (including calcination temperature, calcination time, and residence time), and cooling method, the rutile content, average particle size, and appearance morphology of the sulfuric acid process titanium dioxide primary product can be precisely controlled. The titanium dioxide primary product produced by this method is beneficial to improving the application performance indicators of the product, is more suitable for ink-specific systems, and is beneficial to improving the product's brightness, whiteness, and hiding power, etc., and has good application and promotion prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117902622B_ABST
    Figure CN117902622B_ABST
Patent Text Reader

Abstract

The present application relates to the production technology field of the initial product in the sulphuric acid method titanium white process, and particularly relates to a particle size and morphology control method of the initial product of the ink special sulphuric acid method titanium white, which comprises three steps of salt treatment addition, slurry calcination and cooling. By adjusting the parameters such as the added type and amount of the salt treatment agent, the calcination step and the cooling mode, the rutile content, the average value of the initial product particle size and the appearance morphology of the sulphuric acid method titanium white initial product are accurately controlled, which is more suitable for the ink special system, is beneficial to improving the application performance indexes such as the brightness, the whiteness and the hiding power of the product, and has a good application and promotion prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of raw material production technology in the sulfuric acid process for titanium dioxide, specifically to a method for controlling the particle size and morphology of raw materials for sulfuric acid process titanium dioxide used in ink production. Background Technology

[0002] Titanium dioxide, commonly known as titanium white, is chemically and physically stable, non-toxic, and harmless. It possesses excellent optoelectronic properties, including high refractive index, optimal opacity, and superior whiteness and gloss, making it the world's best white pigment. It is widely used in coatings, plastics, papermaking, inks, and electronics. In ink applications, titanium dioxide products require high whiteness, high gloss, and high hiding power. Currently, high-end titanium dioxide products for ink applications are mainly derived from the sulfate process. The particle size and morphology of this sulfate process titanium dioxide precursor fundamentally determine the final product's whiteness, gloss, and hiding power.

[0003] In the effects of salt treatment agents on titanium dioxide particles, zinc-based salts cause the particles to grow along the shorter direction, resulting in titanium dioxide precursors with better sphericity. Conversely, aluminum-based salts cause the particles to grow along the longer direction, leading to poorer sphericity and making the particles "longer." Currently, high-end ink-grade titanium dioxide precursors often use aluminum-based rather than zinc-based salts. When the average particle size of the calcined precursor is between 200 and 230 nm, and the sphericity is less than 1.4, the finished ink-grade titanium dioxide exhibits superior application performance. Therefore, precisely adjusting the aluminum-based salt treatment agent in conjunction with the calcination process to obtain calcined precursors that meet the requirements for high-end ink-grade titanium dioxide has become an urgent problem to be solved.

[0004] Patent CN107032395B discloses a salt treatment method for titanium dioxide production, comprising the following steps: a) stirring and slurrying water in metatitanic acid; b) adding specific potassium, phosphate, tin, and aluminum salts to the metatitanic acid; c) filtering, collecting the filter cake, and calcining to obtain primary titanium dioxide. This method improves the tinting strength and quality of the titanium dioxide obtained after treatment by using specific treatment agents and their dosages. However, the salt treatment method proposed above does not specify a particular application for the primary titanium dioxide product and lacks specialization. Furthermore, the added salt treatment agents and calcination process significantly affect the particle size distribution and appearance of the final calcined primary product, and this method does not address these aspects.

[0005] Patent CN106946287B discloses a method for precisely controlling the particle size of raw titanium dioxide. This method includes three steps: titanium liquid hydrolysis, metatitanate treatment, and calcination. During titanium liquid hydrolysis, parameters such as the initial concentration of the titanium liquid, stirring speed, and heating temperature and time are adjusted. During metatitanate treatment, the type and content of the salt used are adjusted. Calcination is divided into three stages, with precise control of the calcination temperature and time at each stage, thereby precisely controlling the particle size of the raw titanium dioxide. This method can effectively control the average particle size of raw titanium dioxide within the range of 250-270 nm, resulting in raw titanium dioxide with high scattering power and good optical properties, suitable for general-purpose titanium dioxide used in coatings and other fields. However, the aforementioned disclosed method for precisely controlling the particle size of raw titanium dioxide obtained using the sulfuric acid method also controls the average particle size within the range of 250-270 nm, suitable for general-purpose titanium dioxide used in coatings, but not meeting the average particle size requirements for raw titanium dioxide specifically for inks. Therefore, the existing technology still needs improvement. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention proposes a method for controlling the particle size and morphology of primary titanium dioxide produced by the sulfuric acid process for ink production. This method aims to solve the problem that existing methods for precisely controlling the particle size of primary titanium dioxide are insufficient to meet the requirements of high-end titanium dioxide for ink production.

[0007] The present invention provides a method for controlling the particle size and morphology of primary titanium dioxide produced by the sulfuric acid process for ink production, comprising the following steps: a. Metatitanate treatment process: Salt treatment agent solutions containing aluminum, phosphorus and potassium were added to the filtered metatitanic acid solution. The metatitanic acid solution after adding the salt treatment agent solution was stirred to mix it evenly, and salt-treated metatitanic acid was obtained. b. Calcination process: The metatitanic acid obtained in step a after salt treatment is calcined in three stages. The first stage of calcination removes water from the metatitanic acid; the second stage of calcination removes sulfur from the metatitanic acid; and the third stage of calcination converts the metatitanic acid into rutile titanium dioxide primary product, while the rutile titanium dioxide primary product crystals grow to the required particle size and appearance of the product. c. Cooling process: The high-temperature rutile titanium dioxide precursor obtained in step b is cooled to obtain titanium dioxide precursor.

[0008] Further, in step a, the amount of aluminum added is 0.1% to 0.2% of the mass of metatitanic acid based on TiO2, the amount of phosphorus added is 0.05% to 0.15% of the mass of metatitanic acid based on TiO2, and the amount of potassium added is 0.10% to 0.15% of the mass of metatitanic acid based on TiO2.

[0009] Furthermore, in step b, the first stage of calcination is increased from room temperature to 400~450℃, and the heating process lasts for 1~2 hours. After the temperature reaches the target temperature, it is maintained at the target temperature for 0.5~1.5 hours.

[0010] Furthermore, in the second stage of calcination, the temperature is raised to 720~780℃, and after the temperature reaches the target temperature, it is maintained at the target temperature for 0.5~1.5h.

[0011] Furthermore, in the third stage of calcination, the temperature is raised to 880~920℃, and after the temperature reaches the target temperature, it is maintained at the target temperature for 0.5~1.5h.

[0012] Furthermore, the temperature and time in the final stage of the calcination process in step b work together to achieve a rutile conversion rate of 97.5% to 99.5% in the initial calcined product before the calcination enters the cooling stage.

[0013] Furthermore, in step c, when the temperature is above 600℃, the cooling rate is greater than 200℃ / min.

[0014] Furthermore, in step a, there is no requirement for the order in which the salt treatment agent solution containing aluminum, phosphorus and potassium is added to the filtered metatitanic acid solution.

[0015] Furthermore, in step c, the high-temperature rutile titanium dioxide precursor is cooled using a gas-phase method.

[0016] Furthermore, in step a, the salt treatment agent solutions containing aluminum, phosphorus, and potassium are aluminum sulfate, phosphoric acid, and potassium hydroxide solutions, respectively.

[0017] The beneficial effects of this invention are as follows: The method for controlling the particle size and morphology of sulfuric acid process titanium dioxide primary product for ink production proposed in this invention includes three steps: salt treatment and addition, slurry calcination, and cooling. By adjusting parameters such as the type and amount of salt treatment agent added, calcination steps (including calcination temperature, calcination time, and residence time), and cooling method, the rutile content, average particle size, and appearance morphology of the sulfuric acid process titanium dioxide primary product can be precisely controlled. The titanium dioxide primary product produced by this method is beneficial to improving the application performance indicators of the product, is more suitable for ink-specific systems, and is beneficial to improving the product's brightness, whiteness, and hiding power, etc., and has good application and promotion prospects. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other embodiments can be obtained based on these drawings without creative effort.

[0019] Figure 1 The flowchart illustrates a method for controlling the particle size and morphology of primary titanium dioxide produced by the sulfuric acid process for ink production, provided by an embodiment of the present invention. Figure 2 A preliminary SEM image obtained using an embodiment of the present invention is shown. Detailed Implementation

[0020] It should be understood that the embodiments of the invention shown in the exemplary embodiments are merely illustrative. Although only a few embodiments have been described in detail in this invention, those skilled in the art will readily recognize that various modifications are possible without substantially departing from the teachings of the invention. Accordingly, all such modifications should be included within the scope of the invention. Other substitutions, modifications, variations, and deletions can be made to the design, operating conditions, and parameters of the following exemplary embodiments without departing from the spirit of the invention.

[0021] This invention provides a method for controlling the particle size and morphology of primary titanium dioxide produced by the sulfuric acid process for ink production, comprising the following steps: a. Metatitanate treatment process: Salt treatment agent solutions containing aluminum, phosphorus, and potassium were added to the filtered metatitanic acid solution. The metatitanic acid solution after adding the salt treatment agent solution was stirred to mix it evenly, thus obtaining salt-treated metatitanic acid.

[0022] b. Calcination process: The metatitanic acid obtained in step a after salt treatment is calcined in three stages. The first stage of calcination removes water from the metatitanic acid; the second stage of calcination removes sulfur from the metatitanic acid; and the third stage of calcination converts the metatitanic acid into rutile titanium dioxide primary product, while the rutile titanium dioxide primary product crystals grow to the required particle size and appearance of the product.

[0023] c. Cooling process: The high-temperature rutile titanium dioxide precursor obtained in step b is cooled to obtain titanium dioxide precursor.

[0024] This method includes three steps: salt treatment and addition, slurry calcination, and cooling. By adjusting parameters such as the type and amount of salt treatment agent, calcination steps, and cooling methods, the rutile content, average particle size, and appearance of the primary titanium dioxide produced by the sulfuric acid process can be precisely controlled. The primary titanium dioxide produced using this method is beneficial for improving the application performance indicators of the product, making it more suitable for ink-specific systems. It also helps to improve the product's brightness, whiteness, and hiding power, and has good application and promotion prospects.

[0025] In some embodiments, in step a, the amount of aluminum added is 0.1% to 0.2% of the mass of metatitanic acid based on TiO2, the amount of phosphorus added is 0.05% to 0.15% of the mass of metatitanic acid based on TiO2, and the amount of potassium added is 0.10% to 0.15% of the mass of metatitanic acid based on TiO2.

[0026] In some embodiments, the first stage of calcination in step b is increased from room temperature to 400~450°C, the heating process lasts for 1~2 hours, and after the temperature reaches the target temperature, the target temperature is maintained for 0.5~1.5 hours.

[0027] In some embodiments, the second-stage calcination process continues to raise the temperature to 720~780°C based on the temperature of the first-stage calcination process, and after the temperature reaches the target temperature, it is maintained at the target temperature for 0.5~1.5 hours.

[0028] In some embodiments, the third-stage calcination process raises the temperature to 880~920°C based on the temperature of the second-stage calcination process, and after the temperature reaches the target temperature, it is maintained at the target temperature for 0.5~1.5 hours.

[0029] In some embodiments, the temperature and time in the final stage of the calcination process in step b are coordinated to achieve a rutile conversion rate of 97.5%~99.5%, an average particle size controlled at 200~230nm, and a sphericity of titanium dioxide particles controlled at 1.2~1.4 before the calcination enters the cooling stage. The resulting titanium dioxide precursor, when applied to a titanium dioxide-specific ink system, exhibits superior application indicators such as whiteness, brightness, and hiding power.

[0030] In some embodiments, in step c, when the temperature is above 600°C, the cooling rate is greater than 200°C / min. The purpose of this cooling method is to prevent the titanium dioxide particles from continuing to grow at high temperatures during natural cooling, thereby improving the controllability of the initial particle size and morphology.

[0031] In some embodiments, in step a, the order in which the salt treatment agent solution containing aluminum, phosphorus and potassium is added to the filtered metatitanic acid solution is not required.

[0032] In some embodiments, step c involves rapidly cooling the high-temperature rutile titanium dioxide precursor using a gas-phase method. The purpose of rapid cooling is to prevent the titanium dioxide particles from continuing to grow at high temperatures during natural cooling, thereby improving the controllability of the particle size and morphology of the titanium dioxide precursor. Specifically, the gas-phase method is a technique for synthesizing nano-titanium dioxide by burning carbon monoxide. Metered amounts of oxygen and carbon monoxide are fully combusted in a burner to generate a high-temperature oxygen-rich stream, which is rapidly mixed with high-temperature titanium tetrachloride vapor. The mixture is then cooled after the reaction. Due to the high stability of rutile, this method is particularly suitable for its processing.

[0033] In some embodiments, the salt treatment agent solution containing aluminum, phosphorus, and potassium is aluminum sulfate, phosphoric acid, and potassium hydroxide solution, respectively.

[0034] The present invention will be described in detail below with reference to specific embodiments: Example 1 The following method is used to produce a primary product of sulfuric acid process titanium dioxide that meets the requirements for high-end inks. The specific operating steps are as follows: a. Metatitanate treatment process Aluminum sulfate, phosphoric acid, and potassium hydroxide solutions were added to the filtered metatitanic acid solution in any order. The amount of aluminum added to the aluminum sulfate solution was 0.10% of the metatitanic acid mass (based on TiO2), the amount of phosphorus added to the phosphoric acid solution was 0.05% of the metatitanic acid mass (based on TiO2), and the amount of potassium added to the potassium hydroxide solution was 0.10% of the metatitanic acid mass (based on TiO2). The metatitanic acid solution after adding the salt treatment agent was stirred until homogeneous, yielding salt-treated metatitanic acid.

[0035] b. Calcination process The metatitanic acid obtained in step a after salt treatment is calcined in stages. The first stage involves increasing the temperature from room temperature to 400°C for 1 hour, then maintaining the target temperature for 0.5 hours. This stage aims to remove water from the metatitanic acid. The second stage involves further heating to 720°C for 1 hour, then maintaining the target temperature for 0.5 hours. This stage aims to remove sulfur from the metatitanic acid. The third stage involves heating to 880°C for 1 hour, then maintaining the target temperature for 0.5 hours. This stage aims to convert the metatitanic acid into rutile titanium dioxide, while simultaneously allowing the initial rutile titanium dioxide crystals to grow to the desired particle size and morphology.

[0036] c. Cooling process The high-temperature titanium dioxide precursor obtained in step b is cooled. The cooling process requires a rapid cooling method. After cooling, the titanium dioxide precursor is obtained.

[0037] The calcined initial product obtained using these parameters, after testing, showed a rutile conversion rate of 97.5%, a statistically obtained average particle size of 220 nm, a particle size standard deviation of 71 nm, and a sphericity of 1.20.

[0038] Example 2 The following method is used to produce a primary product of sulfuric acid process titanium dioxide that meets the requirements for high-end inks. The specific operating steps are as follows: a. Metatitanate treatment process Aluminum sulfate, phosphoric acid, and potassium hydroxide solutions were added to the filtered metatitanic acid solution in any order. The amount of aluminum added to the aluminum sulfate solution was 0.20% of the metatitanic acid mass (based on TiO2), the amount of phosphorus added to the phosphoric acid solution was 0.15% of the metatitanic acid mass (based on TiO2), and the amount of potassium added to the potassium hydroxide solution was 0.15% of the metatitanic acid mass (based on TiO2). The metatitanic acid solution after adding the salt treatment agent was stirred until homogeneous, yielding salt-treated metatitanic acid.

[0039] b. Calcination process The metatitanic acid obtained in step a after salt treatment is calcined in stages. The first stage involves increasing the temperature from room temperature to 450°C for 2 hours, maintaining this temperature for 1.5 hours after reaching the target temperature. This stage aims to remove water from the metatitanic acid. The second stage involves further heating to 780°C for 1 hour, maintaining this temperature for 1.5 hours after reaching the target temperature. This stage aims to remove sulfur from the metatitanic acid. The third stage involves heating to 920°C for 1 hour, maintaining this temperature for 1.5 hours after reaching the target temperature. This stage aims to convert the metatitanic acid into rutile titanium dioxide, while simultaneously allowing the initial rutile titanium dioxide crystals to grow to the desired particle size and morphology.

[0040] c. Cooling process The high-temperature titanium dioxide precursor obtained in step b is cooled. The cooling process requires a rapid cooling method. After cooling, the titanium dioxide precursor is obtained.

[0041] The calcined initial product obtained using these parameters, after testing, showed a rutile conversion rate of 99.5%, a statistically obtained average particle size of 230 nm, a particle size standard deviation of 79 nm, and a sphericity of 1.40.

[0042] Example 3 The following method is used to produce a primary product of sulfuric acid process titanium dioxide that meets the requirements for high-end inks. The specific operating steps are as follows: a. Metatitanate treatment process Aluminum sulfate, phosphoric acid, and potassium hydroxide solutions were added to the filtered metatitanic acid solution in any order. The amount of aluminum added to the aluminum sulfate solution was 0.15% of the metatitanic acid mass (based on TiO2), the amount of phosphorus added to the phosphoric acid solution was 0.10% of the metatitanic acid mass (based on TiO2), and the amount of potassium added to the potassium hydroxide solution was 0.10% of the metatitanic acid mass (based on TiO2). The metatitanic acid solution after adding the salt treatment agent was stirred until homogeneous, yielding the salt-treated metatitanic acid.

[0043] b. Calcination process The salt-treated metatitanic acid obtained in step a is calcined in stages. The first stage involves increasing the temperature from room temperature to 420°C for 1 hour, then maintaining the target temperature for 1.5 hours. This stage aims to remove water from the metatitanic acid. The second stage involves further heating to 760°C for 1 hour, then maintaining the target temperature for 0.5 hours. This stage aims to remove sulfur from the metatitanic acid. The third stage involves heating to 900°C for 1 hour, then maintaining the target temperature for 1.5 hours. This stage aims to convert the metatitanic acid into rutile titanium dioxide, while simultaneously allowing the crystals to grow to the desired particle size and morphology.

[0044] c. Cooling process The high-temperature titanium dioxide precursor obtained in step b is cooled. The cooling process requires a rapid cooling method. After cooling, the titanium dioxide precursor is obtained.

[0045] The calcined initial product obtained using these parameters, after testing, showed a rutile conversion rate of 98.9%, a statistically obtained average particle size of 221 nm, a particle size standard deviation of 75 nm, and a sphericity of 1.31.

[0046] The results of the implementation examples show that the method for controlling the particle size and morphology of titanium dioxide primary products produced using the sulfuric acid process of this invention can produce high-end aluminum-based titanium dioxide primary products for inks. These products exhibit a rutile conversion rate between 97.5% and 99.5%, an average particle size between 200 and 230 nm, and a sphericity of titanium dioxide particles between 1.2 and 1.4. This titanium dioxide primary product is beneficial for improving the application performance indicators of products and is highly suitable for ink-specific systems.

[0047] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A method for controlling the particle size and morphology of primary titanium dioxide produced by the sulfuric acid process for ink production, characterized in that, Includes the following steps: a. Metatitanate treatment process: Salt treatment agent solutions containing aluminum, phosphorus, and potassium were added to the filtered metatitanic acid solution. The metatitanic acid solution after adding the salt treatment agent solutions was stirred until it was mixed evenly to obtain salt-treated metatitanic acid. The amount of aluminum added was 0.1% to 0.2% of the mass of metatitanic acid based on TiO2, the amount of phosphorus added was 0.05% to 0.15% of the mass of metatitanic acid based on TiO2, and the amount of potassium added was 0.1% to 0.15% of the mass of metatitanic acid based on TiO2. b. Calcination process: The metatitanic acid obtained in step a after salt treatment was calcined in three stages. The first stage removed water from the metatitanic acid; the second stage removed sulfur; and the third stage converted the metatitanic acid into rutile titanium dioxide precursor. Simultaneously, the rutile titanium dioxide precursor crystals grew to the required particle size and morphology for the product: the average particle size of the titanium dioxide particles was controlled to be 200-230 nm, and the sphericity of the titanium dioxide particles was controlled to be 1.2-1.

4. The first stage of calcination involves increasing the temperature from room temperature to 400-450℃, with the heating process lasting 1-2 hours. Once the target temperature is reached, it is maintained at that temperature for 0.5-1.5 hours. In the second stage of calcination, the temperature continues to rise to 720~780℃. After the temperature reaches the target temperature, it is maintained at the target temperature for 0.5~1.5 hours. In the third stage of calcination, the temperature is raised to 880~920℃, and after the temperature reaches the target temperature, it is maintained at the target temperature for 0.5~1.5h. c. Cooling process: The high-temperature rutile titanium dioxide precursor obtained in step b is cooled to obtain titanium dioxide precursor. The high-temperature rutile titanium dioxide precursor is rapidly cooled using a gas-phase method. When the temperature is above 600℃, the cooling rate is greater than 200℃ / min.

2. The method for controlling the particle size and morphology of primary titanium dioxide produced by sulfuric acid process for ink production according to claim 1, characterized in that, In step b, the temperature and time in the final stage of the calcination process work together to achieve a rutile conversion rate of 97.5% to 99.5% in the initial calcined product before the calcination enters the cooling stage.

3. The method for controlling the particle size and morphology of primary titanium dioxide produced by sulfuric acid process for ink production according to claim 1, characterized in that, In step a, there is no requirement for the order in which the salt treatment agent solution containing aluminum, phosphorus and potassium is added to the filtered metatitanic acid solution.

4. The method for controlling the particle size and morphology of primary titanium dioxide produced by the sulfuric acid process for ink production according to claim 1, characterized in that, In step a, the salt treatment agent solutions containing aluminum, phosphorus, and potassium are aluminum sulfate, phosphoric acid, and potassium hydroxide solutions, respectively.

Citation Information

Patent Citations

  • Precise control method for particle size of titanium dioxide raw materials

    CN106946287B

  • Salt treatment methods during titanium dioxide production

    CN107032395B

  • Method for recycling before-kiln dehydration filtrate and method for producing titanium dioxide

    CN103232065A